Management of intersection syndrome in professional motorcycle rider: a case report - Marenghi, Letizia; Mainardi, Giulia; Zasa, Michele (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Intersection syndrome is an uncommon and underdiagnosed condition, especially found in sport overuse. This case report describes the treatment of a professional motor biker who presented intense wrist pain and swelling after training sessions. Methods: The athlete was treated with rest, the use of a wrist splint combined with NSAIDs, physical therapy, including pulsed Nd-YAG laser therapy and exercise, such as stretching and release, massage and eccentric training. Results: The applied therapeutic protocol was successful and allowed the biker to completely resolve the symptoms and return to training session and professional races at full power. The results are durable at 5 months post injury follow up. Conclusions: This experience suggests that pulsed Nd-YAG laser therapy can be an additional useful tool in the global approach treatment for intersection syndrome, contributing with splint and manual therapy, to full recovery even in mechanically stressful conditions. (www.actabiomedica.it)